Erythropoietin Attenuates Experimental Contrast-Induced Nephrology: A Role for the Janus Kinase 2/Signal Transducer and Activator of Transcription 3 Signaling Pathway - Yang, Jia; Zhou, Jiaojiao; Wang, Xin; Ji, Ling; Wang, Siwen; Chen, Xuelian; Yang, Lichuan (Frontiers in Medicine, 2021)
The aim of the present study was to investigate the effect of erythropoietin on contrast-induced nephrology (CIN) in vivo and vitro. Male C57/BL6J mice were divided into four groups: control, CIN (iohexol 6.0 g/kg), erythropoietin (EPO 3000 IU/kg) and CIN+EPO. Hematoxylin and eosin(HE) staining and biochemical index analysis were performed to evaluate renal injury. The cellular proliferation rate was detected using Cell Counting Kit‑8 (CCK8) assay. In addition, TdT mediated dUTP nick end labeling (TUNEL) assay and flow cytometric assay were used to assess the apoptosis of tissue and cells respectively. Renal protein expressions associated with apoptosis and signing pathway were determined by western blot (WB) assay in tissue and cells. The results showed that EPO significantly decreased serum creatinine, blood urea nitrogen and cystatin C levels, and alleviated renal histological changes in vivo. The protein levels of Janus kinase2/signal transducer and activator of transcription3 (JAK2/STAT3) pathway components were overexpressed in group with treatment of EPO. Furthermore, EPO could suppress cell apoptosis rate, decrease protein levels of cleaved caspase-3 and Bax, and enhance the expression of Bcl-2. In summary, EPO could exert renoprotection effect by activating JAK2/STAT3 signaling pathway, which may be a novel potential therapy for the treatment of CIN in clinic.